Renormalized solutions for some nonlinear nonhomogeneous elliptic problems with Neumann boundary conditions and right hand side measure - Elhoussine Azroul; Mohamed Badr Benboubker; Rachid Bouzyani; Houssam Chrayteh (Boletim da Sociedade Paranaense de Matemática, 2020)
Our aim in this paper is to study the existence of renormalized solution for a class of nonlinear p(x)-Laplace problems with Neumann nonhomogeneous boundary conditions and diuse Radon measure data which does not charge the sets of zero p(.)-capacity